Reinterpreting Ramayana: The (Re)Production of the Meanings of Power in “Ramayana”, an East Javanese Shadow Puppet Performance Text - R., Basuki; D., Setiawan (k@ta: A Biannual Publication on the Study of Language and Literature, 2012)
In this article we discuss the meanings of power that are produced/reproduced in an East Javanese shadow puppet show entitled Ramayana by Ki Sinarto. In Foucauldian perspective, the meanings of power are constantly intertwined with other issues, and in Ki Sinarto’s Ramayana they are closely related to the state, revelation/women, family, and people. Despite the puppeteer’s efforts in doing a 'subversive interpretation' of Ramayana, the Javanese concept of power still ‘overpowers’ his discourse. Addressing the contemporary Indonesian state, Ki Sinarto is propagating the concept of Javanese power from the late Mataram kingdom. He also proposes that women can have a legitimizing power as the bearers of revelation, but the discourse of women as distractors to men’s career still surfaces. Ki Sinarto further pictures the main conflict of Ramayana as a dispute of an aristocratic family instead of woman. Finally, the relations between Javanese people and their leaders are not necessarily straightforward and linear